Assessing the Level of Awareness about Predatory Journal among the Students of IAAS, Paklihawa - Rana, C.; Tiwari, C. K.; Bhattarai, B.; Gautam, A.; K.C., B.; Khanal, A.; Sharma, A.; Tiwari, B.; Gautam, A.; Parajuli, A.; Kaphle, K. (Journal of the Institute of Agriculture and Animal Science, 2020)
The predatory journal has emerged as a threat to credible scientific researches and publication practices because of its ill-money-draining mentality by attracting the authors for publication without providing mandatory peer-review, low publication standard, editorial, and publishing services. This study’s main objective is to assess the level of awareness about predatory journals among students of the Institute of Agriculture and Animal Science (IAAS) as a hope to support scholarly communication in battling unprofessional conduct. We conducted an online crosssectional survey from 26th June to 6th July 2020 at IAAS. A structured questionnaire loaded in Google form was circulated online via E-mails, social media messages, and posted on various IAAS pages. With a total of 110 respondents from the veterinary and agriculture science students, the data concluded that among all respondents only 66.4% were familiar with the idea of predatory journals whereas only 38.2% of respondents were aware of Beall’s list and its concept. This fails in a published article to meet the criteria in the scientific community. Hence, proper knowledge regarding the nature of the journal is necessary for publishing the paper so that the scholarly work could reach its milestone.